Application of integrated spatial approaches for studying the vegetation alternation's effect on the reclaimed land of contaminated zinc mine - K. Somprasong (2019)
© 2019 Published under licence by IOP Publishing Ltd. The Mae Tao basin, Thailand has been considered to be a remote cadmium (Cd) - contaminated area since 2002. This area has been reported as the largest zinc deposition area so that the explicit potential cadmium source has not been detected. According to the reports from both government and private sectors, the zinc mine in the middle of the basin were determined to be one of the cadmium contributors in the area. From 2014, the mine closure operation has been conducted, thus the study on the selection of cover vegetation in the area has not been accomplished. In this study, the integrated approaches between MINESITE 3D, Geographic Information System (GIS) application and remote sensing techniques, were assigned to simulate the repetition of the vegetation over the reclaimed area. The study demonstrates that using the grass type vegetation for the reclamation of the area can largely reduce the potential erosion of the mine with a range from 89.70 to 94.45%. The results also demonstrate that the young vetiver grass cannot effectively reduce the potential erosion. Additionally, the study on the development of the supporting practice over the mining production area should be further conduct.